ANALISIS IMPLEMENTASI INTEGRASI JAMINAN KESEHATAN DAERAH(JAMKESDA) KE DALAM JAMINAN KESEHATAN NASIONAL (JKN) DI PROVINSI JAWA TENGAH - Nuraini Maulidna; Putri Asmita Wigati; Anneke Suparwati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Act number 40 year 2004about  SJSN is an attempt to build a Universal Health Coverage (UHC) in 2019.  The implemention of medical insurance which is currently happen is not suitable with the policy so formed Jamkesda into JKN. But, since the beginning of January 2016, there are 12 district s/ towns not integrated yet into JKN from 35 districts/towns in Central Java Province. The purpose of this research is to analysis the implemention of the integration Jamkesda to JKN in Central Java. The research is qualitative study by descriptive approach. Data collection is carried out by Indepth Interview and secondary data collection that related. The first informant are representatives of Health provincial health office Central Java , Social Affairs representative Central Java Province , and Bappeda Central Java Province. The validity test of triangulation with the Klaten Health Office and the Semarang city's Health Office. The result of this researches known that the province of central java doesn’t have an indicator for the implementation of the integration Jamkesda to JKN. From the aspect of communication, there are those who do not care about coordination, strategy which is Juknis undelivered well, and the budget which is lacking the sufficient number of target participants. Bureaucratic structure has been good enough but the SOP of Jamkesda integration to JKN not yet available. The suggestion for this researches are consistency participants,carry out advocacy efforts, emphasizes an understanding of regulation, establish SOP integration, collect data more intens,and recommendation for research of policy impact.